The Inequality of Right and Obligation of Minangkabau Men in Matrilineal System - Sri Meiyenti; Afrida Afrida (Jurnal Ilmu Sosial Mamangan, 2018)
Matrilineal in Minangkabau is well-known, especially by social scientists. This research is also deal with matrilineal in Minangkabau society. It specifically focuses on the position of men in the matrilineal andtheir view of the position.This research was conducted in Padang by a qualitative method. Data were collected from participant observations and in-depth interview. Research findings showed that Minangkabau men experienced an imbalance between obligations and rights in kinship.They were honored as the leader of their relative through some social and economic responsibilities. On the other hand, they did not have a complete right to the economic resources that are controlled by the woman. The men were discriminated against based on this regulation. There are massive differences between men and women related to the legacy. There were numerous abandoned men in their old age. However, the Minangkabau men did not consider it because of the effect of matrilineal customs.